Multi Targeted CAR-T Cell Therapies for B-Cell Malignancies - Shah, Nirav N.; Maatman, Theresa; Hari, Parameswaran; Johnson, Bryon (Frontiers in Oncology, 2019)
Chimeric antigen receptor (CAR) modified T cell therapy has revolutionized the treatment of relapsed and refractory hematological malignancies. Through targeting of the CD19 antigen on B cells durable remissions have been achieved in patients with B cell non-Hodgkin lymphoma and acute lymphoblastic lymphoma. Despite impressive responses, multiple escape mechanisms to evade CAR-T cell therapy have been identified, among which the most common is loss of the target antigen. In this review we will highlight outcomes to date with CD19 CAR-T cell therapy, describe the current limitations of single targeted CAR-T therapies, review identified tumor escape mechanisms, and lastly discuss novel strategies to overcome resistance via multi-targeted CAR-T cells.